Os tons de Zé: transformações paradigmáticas na obra de Tom Zé (1967-1976) - Bomfim, Leonardo Corrêa [UNESP] (2014)
This research broaches part of the work of the composer, arranger, singer, player, writer and performer Antônio José Santana Martins, popularly known as Tom Zé. It was proposed a transdisciplinar analysis about his artistic production placed between the years 1967 and 1976, discussing five records of the musician, revealers of the transition between these two moments, since the beginning of his career (1967) - in his tropicalist phase - until his album Estudando o samba, recorded in 1976. This LP showed large importance because, according to the composer H. J. Koellreutter (1915-2005), it inaugurated - through the music Toc - a new proposal in the compositional structure of the artist, that fits in the Relativistic aesthetics of Imprecise and Paradoxical and in the concept of quadridimensional time of the German theorist. This concept subsequently directed the research to other notions associated with paradigm shifts, observed both in art and in modern science (quantum and relativistic physics) of the XX and XXI centuries. It was sought in this study, to list elements in Tom Zé’s opus consistent with this paradigm shift, in order to understand more deeply the aesthetic and compositional changes of the artist in the time frame selected. As a strictly conventional technical and musical analysis would not be capable to involve this multimidiatic artist’s totality work, his job was also analyzed under aesthetic, historical and socio-political aspects that encompass, justify and can contribute to his music comprehension. Therefore, also the lyrics, performances, clothing were verified, in addition to his discourses; considering even materials like articles, interviews, album covers etc. Thus, it was possible to observe the different nuances and gradations of the composer in his musical transformations